2005
DOI: 10.1073/pnas.0503227102
|View full text |Cite
|
Sign up to set email alerts
|

Golgi targeting of human guanylate-binding protein-1 requires nucleotide binding, isoprenylation, and an IFN-γ-inducible cofactor

Abstract: Human guanylate-binding protein-1 (hGBP-1) is a large GTPase, similar in structure to the dynamins. Like many smaller GTPases of the Ras͞Rab family, it is farnesylated, suggesting it may dock into membranes and perhaps play a role in intracellular trafficking. To date, however, hGBP-1 has never been associated with a specific intracellular compartment. Here we present evidence that hGBP-1 can associate with the Golgi apparatus. Redistribution from the cytosol to the Golgi was observed by immunofluorescence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 52 publications
4
73
1
Order By: Relevance
“…In this framework a recent report on Golgi localization of hGBP-1 in cells co-stimulated with IFN-␥ and AlF suggested that hGBP-1 may be classically secreted. 13 However, under physiological conditions without AlF, no significant Golgi enrichment of hGBP-1 was detected. This does not exclude that Golgi translocation may be important for certain biological functions of hGBP-1, but clearly indicates that the amount of hGBP-1 in the Golgi may be too small to cause the release of significant amounts of hGBP-1 via the classical route.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this framework a recent report on Golgi localization of hGBP-1 in cells co-stimulated with IFN-␥ and AlF suggested that hGBP-1 may be classically secreted. 13 However, under physiological conditions without AlF, no significant Golgi enrichment of hGBP-1 was detected. This does not exclude that Golgi translocation may be important for certain biological functions of hGBP-1, but clearly indicates that the amount of hGBP-1 in the Golgi may be too small to cause the release of significant amounts of hGBP-1 via the classical route.…”
Section: Discussionmentioning
confidence: 97%
“…12 Recently, it has been demonstrated in HeLa cells that hGBP-1 can translocate to the Golgi membranes. 13 The translocation process required the GTPase activity of hGBP-1, stable induction of a protein structure resembling the GTP-bound form [induced by aluminum fluoride (AlF)], a functional isoprenylation signal, and IFN-␥ stimulation of the cells. 13 Presence in vesicles and/or Golgi localization are hallmarks of secreted proteins.…”
mentioning
confidence: 99%
“…For both functions, the ability to interact with cellular membranes is a prerequisite. In the case of hGBP1 and murine GBP2 (mGBP2), abolishing the C-terminal lipid modification results in biologically inactive proteins (26)(27)(28)33). To understand the function and mechanism of hGBP1 on a molecular level, it is therefore of critical importance to study the protein in the lipid modified state.…”
Section: Discussionmentioning
confidence: 99%
“…In IFN-induced cells, hGBP1 is localized in cytosolic puncta, unidentified to date (26,27). The addition of AlFx induces redistribution of hGBP1 to the Golgi complex in a farnesylation-dependent manner (26,28). On the other hand, mutation of the contact between the LG domain and the α12/13 domain results in the localization of hGBP1 at the plasma membrane, whereas a protein mutant impaired in binding nucleotides displays a purely cytosolic staining (12,27).…”
Section: Significancementioning
confidence: 99%
“…The p47 family members are recruited to nascent phagosomes after infection with bacteria and parasites (15). The p65 family member Gbp1 is recruited to the Golgi after chemical activation (20). The potential biological outcome of p47 and p65 activation during microbial infection has been postulated to involve rapid killing/ degradation and trafficking of the pathogen to the antigenprocessing compartments.…”
Section: Discussionmentioning
confidence: 99%